Interleukin-6 Elevation Is a Key Pathogenic Factor Underlying COVID-19-Associated Heart Rate-Corrected QT Interval Prolongation - Lazzerini, Pietro Enea; Accioli, Riccardo; Acampa, Maurizio; Zhang, Wen-Hui; Verrengia, Decoroso; Cartocci, Alessandra; Bacarelli, Maria Romana; Xin, Xiaofeng; Salvini, Viola; Chen, Ke-Su; Salvadori, Fabio; D’errico, Antonio; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background. Heart rate-corrected QT-interval (QTc) prolongation is prevalent in patients with severe coronavirus disease 2019 (COVID-19), and associates with poor outcomes. Recent evidence suggests that the exaggerated host immune-inflammatory response characterizing the disease, specifically interleukin(IL)-6 increase, may have an important role, possibly via direct effects on cardiac electrophysiology. Aim of this study was to dissect the short-term discrete impact of IL-6 elevation on QTc in severe COVID-19 patients and explore the underlying mechanisms. Methods. We investigated: (1) the QTc duration in COVID-19 patients during active phase and recovery, and its association with C-reactive protein (CRP) and IL-6 levels; (2) the acute impact of IL-6 administration on QTc in an in-vivo guinea-pig model; (3) the electrophysiological effects of IL-6 on ventricular myocytes in-vitro. Results. In patients with active severe COVID-19 and elevated IL-6, regardless of acute myocardial injury/strain and concomitant QT-prolonging risk factors, QTc is significantly prolonged, and rapidly normalized in correlation with IL-6 decrease. The direct administration of IL-6 in an in-vivo guinea-pig model acutely prolongs QTc duration. Moreover, ventricular myocytes incubated in-vitro with IL-6 show evident action potential prolongation, along with a significant inhibition of the rapid delayed-rectifier potassium current, IKr. Conclusions. For the first time, we demonstrated that in severe COVID-19, systemic inflammatory activation can per se promote QTc prolongation, via IL-6 elevation leading to ventricular electric remodeling. Despite transitory, such modifications may significantly contribute to arrhythmic events and associated poor outcomes in COVID-19. These findings provide further rationale to current anti-inflammatory treatments for COVID-19, including IL-6-targeted therapies.